'Every day is hard, being outside, but you have to do it for your child': Mixed-methods formative evaluation of a peer-led parenting intervention for homeless families. (October 2020) - Bradley, Caroline; Day, Crispin; Penney, Caroline; Michelson, Daniel
We conducted a mixed-methods, formative evaluation of a peer-led parenting intervention for homeless families. Participants were parents living in temporary accommodation with self-identified difficulties related to parenting an index child aged 2–11 years. An evidence-based programme ('Empowering Parents, Empowering Communities') was adapted for delivery with the target population in London, UK. We assessed feasibility in terms of session attendance rate, intervention completion rate and potential for impact on a range of parent-reported outcomes measures. Acceptability and appropriateness were examined by a user satisfaction measure and qualitative interviews. The intervention was delivered across three group cohorts ( N = 15). Thirteen parents completed the programme (including one parent who required two attempts). We found improvements in child behavioural difficulties, parenting knowledge and practices, while parental well-being and social support were unchanged. Participants were highly satisfied overall, with indications that the peer-led model mitigated negative expectancies of services and normalized experiences of parenting in challenging conditions. Parental self-care and 'the good enough parent' were strongly endorsed topics, although some content (e.g. timeout) was deemed impractical. These promising findings warrant further testing under controlled conditions.